Granular cell tumor of the breast: a multidisciplinary challenge. (December 2019) - Meani, Francesco; Di Lascio, Simona; Wandschneider, Wiebke; Montagna, Giacomo; Vitale, Valerio; Zehbe, Sabine; Harder, Yves; Parvex, Sandra Leoni; Spina, Paolo; Canonica, Claudia; Generali, Daniele; Pagani, Olivia
Graphical abstract: Highlights: Granular cell tumors are rare soft tissue tumors; they are almost never malignant, but can mimic a carcinoma. Differential diagnosis of Granular cell tumors is challenging in particular during follow up in a breast cancer patient. A misdiagnosis due to the fear of local or distant recurrence can be responsible for patient's overtreatment. Despite a nonspecific macroscopic appearance, their histological features and IHC profile are distinctive. Core needle biopsy, followed by microscopic and immunohistochemistry (IHC) evaluation is the diagnostic modality of choice. Treatment consists of radical local excision with margin assessment; no adjuvant therapy is indicated, however after surgical excision follow-up for 10 years is strongly recommended. Abstract: Granular cell tumors are rare soft tissue tumors; they are almost never malignant, but can mimic a carcinoma clinically, radiologically and microscopically. The finding of a suspicious lump often entails subsequent diagnostic procedures that can pose significant anxiety on patients before reaching a challenging differential diagnosis. The physical and psychological burden is even more significant when such findings occur during the follow up of a previous oncologic condition. Sometimes the fear for a potential local or distant recurrence can be responsible for a misdiagnosis and lead to patient overtreatment.